Recycling marble wastes and Jarosite wastes into sustainable hybrid composite materials and validation through Response Surface Methodology - Pappu, Asokan; Thakur, Vijay Kumar; Patidar, Ravi; Asolekar, Shyam R.; Saxena, Mohini (Elsevier, 2019)
During marble processing such as cutting, polishing and grinding, a considerable amount of fine residues refereed as marble processing rejects (MPRs) are produced and have become a serious environmental issue. So the current study deals with the conversion of MPRs into hybrid ceramic composite bricks (CCB) with Jarosite waste in a clay matrix system. Mix design and optimization of CCB was performed to illustrate the potentials of MPRs and Jarosite wastes as low-cost high-value composites materials. Response Surface Methodology (RSM) model was also used in this work for simulation and to optimize the process for improving CCB quality employing classic mixture approach. Detoxification through mineralogical changes was achieved during firing composite bricks at 960 °C ± 2 °C and was confirmed using the XRD analysis. Compressive strength of CCB using 15% MPRs with 1:1 Jarosite waste - clay matrix ratio met the standard quality (>35 kg/cm2) for its use in construction purpose. It is evident from the RSM model results and statistical analysis for the response compressive strength, shrinkage, water absorption capacity, density and leachate concentration of Cd as well as Pb in the CCB is in laudable agreement with actual experimental performance.
Keywords: Marble processing residues; Hazardous Jarosite waste; Hybrid composite; Response surface methodology; Optimization; Toxic substances; Mechanical properties; Sintering mechanism